Prediction of mechanical ventilation greater than 24 hours in critically ill obstetric patients: ten years of data from a tertiary teaching hospital in mainland China - Huiying Zhao; Guangjie Wang; Jie Lyu; Xiaohong Zhang; Youzhong An (BMC, 2021)
Abstract Background Maternal admission to the intensive care unit (ICU) during pregnancy or in the postpartum period is a marker of severe acute maternal morbidity. Mechanical ventilation is an important and basic method of maintaining life support in the ICU, but prolonged mechanical ventilation (PMV) is associated with a prolonged length of hospital stay and other adverse outcomes. Therefore, we conducted this retrospective study to describe morbidity and further try to identify the risk factors for PMV in critically ill obstetric women. Methods The clinical data were obtained from a single-centre retrospective comparative study of 143 critically ill obstetric patients at a tertiary teaching hospital in mainland China between January 1, 2009, and December 31, 2019. PMV was defined as a mechanical ventilation length of more than 24 h. Clinical and obstetric parameters were collected to analyse the risk factors for PMV. Patients were separated into groups with and without PMV. Potential risk factors were identified by univariate testing. Multivariate logistic regression was used to evaluate independent predictors of PMV. Results Out of 29,236 hospital deliveries, 265 critically ill obstetric patients entered the ICU. One hundred forty-five (54.7%) of them were treated with mechanical ventilation. Two were excluded because of death within 24 h. Sixty-five critically ill obstetric patients (45.5%) underwent PMV. The independent risk factors for PMV included estimated blood loss (odds ratio (OR) =1.296, P=0.029), acute kidney injury (AKI) (OR=4.305, P=0.013), myocardial injury (OR=4.586, P=0.012), and PaO2/FiO2 (OR=0.989, P< 0.001). The area under the receiver operating characteristic (ROC) curve based on the predicted probability of the logistic regression was 0.934. Conclusions Estimated blood loss, AKI, myocardial injury, and PaO2/FiO2 were independent risk factors for PMV in critically ill obstetric patients.